(untitled) (Vintage Books)
Even as he tells the stories of such individual creators as Homer, Joyce, Giotto, Picasso, Handel, Wagner, and Virginia Woolf, Boorstin assembles them into a grand mosaic of aesthetic and intellectual invention. In the process he tells us not only how great art (and great architecture and philosophy) is created, but where it comes from and how it has shaped and mirrored societies from Vedic India to the twentieth-century United States.
Keywords: Văn minh,Civilization; Lịch sử,History